DESAIN MODEL PEDAGOGI PENDIDIKAN KEWARGANEGARAAN LINGKUNGAN HIDUP PADA PENDIDIKAN DASAR - Hidayat, Nuris; Bagus Sanjaya, Dewa; I Nengah Suastika (STAI Ma'had Aly Al-Hikam Malang, 2025)
Education for environmental citizenship plays an important role in social change towards sustainable development, achieving economic, social and environmental balance through informed, cooperative and participatory citizens. The purpose of this study is to develop a design model for educational pedagogy for environmental citizenship in primary education. The method used in this study uses a literature review on the topic (articles, and curriculum guidelines for primary education). The results of the study propose a conceptual framework for developing a model of educational pedagogy for environmental citizenship. The framework consists of important aspects of variables that can be considered in the learning environment such as exploring the environment, analyzing problems, explaining facts, recommending solutions, outlining actions, and reflecting and listening.